Effects of Maternal Age and Parenting Stress on the Social-Emotional Development of Young Children - Maulidiyah, Eka Cahya; Fitri, Ruqoyyah; Reza, Muhammad; Fadzil, Alivia Nur (Universitas Pendidikan Ganesha, 2025)
Maternal age maturity and parenting stress are critical factors influencing the social-emotional development of young children, as parenting practices play a key role in shaping how children learn to regulate emotions and build social relationships. In practice, parents often encounter various challenges in child-rearing, requiring psychological maturity and effective emotional regulation to ensure optimal child development. This study aims to analyze the effects of maternal age and parenting stress on the social-emotional development of early childhood. A quantitative approach with an ex-post facto design was employed, using purposive sampling techniques. The research subjects consisted of 100 mothers and their children aged 5–6 years. Data were analyzed through multiple linear regression using t-tests and F-tests. The results indicate that maternal age and parenting stress significantly affect the social-emotional development of young children. These findings highlight that greater maternal maturity and lower levels of parenting stress contribute positively to children’s social-emotional growth. The study implies the importance of providing support for parents, particularly in managing stress and improving parenting quality, to foster children’s optimal development.